Incidencia de la estimulación temprana en el desarrollo de la sensopercepción visual en niños 3 a 4 años de la sala de estimulación de acción social Gad Guaranda, provincia Bolívar, periodo 2021-2022. - Almeida Chafla, David Esteban (2022)
In the first part of this investigation you will fine the following points: the dedication, the gratitude, the tutor's certificate, the notarized authorship and the index of which was The second part is the introduction of the project, the theme, the background, the problem with it’s description and the formulation of the problem, the justification of why this research is carried out, the general and specific objective of the project to treat and the theoretical framework that is formed by scientific theory, legal theory and referential theory. In the final part of the research project is the methodological framework that was used, which includes the research approach, design or type of study, methods, data collection instruments, the universe and sample, the analysis of the results, conclusions, proposal, bibliography and annexes of this project